2021
DOI: 10.1111/and.14308
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of erectile dysfunction in Egyptian individuals after contracting COVID‐19: A prospective case–control study

Abstract: This study aimed to screen healthy individuals who contracted COVID‐19 for erectile dysfunction (ED) and to determine the potential risk factors that can predict ED in these individuals. One hundred and seven cases versus 90 controls agreed to participate in the study. Two structured interviews with 1 month interval were conducted. All participants were evaluated by the validated Arabic version of the international index of erectile function (IIEF‐5) and assessment of the psychological state by Hamilton depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
(61 reference statements)
0
8
1
1
Order By: Relevance
“…Saad et al demonstrated a significant difference in the mean IIEF-5 score between patients with COVID-19 and controls. Their multiple logistic regression model for COVID-19 ED revealed that the IIEF-5 score was an independent variable (29). Nevertheless, the results of this study found no association between IIEF-5 score and men recovering from COVID-19.…”
Section: /Mlcontrasting
confidence: 66%
“…Saad et al demonstrated a significant difference in the mean IIEF-5 score between patients with COVID-19 and controls. Their multiple logistic regression model for COVID-19 ED revealed that the IIEF-5 score was an independent variable (29). Nevertheless, the results of this study found no association between IIEF-5 score and men recovering from COVID-19.…”
Section: /Mlcontrasting
confidence: 66%
“…Since the beginning of the COVID-19 pandemic, there has been growing evidence of the increasing prevalence of ED in male individuals, either following the infection and/or resulting from the psychological stress associated with the pandemic 29 , 30 , 31 , 32 . Although there is increasing evidence that the pandemic has had a serious effect on sleep, little is known about how these sleep disturbances could be linked with the reported increase in the incidence of ED.…”
Section: Resultsmentioning
confidence: 99%
“…Other risk factors that could not be analyzed using meta-analysis are listed in Table S4. The study also found that COVID-19 was one of the risk factors for ED, and OR was higher with increasing severity of illness [ 32 , 33 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Saad et al . [ 32 ] showed that smoking, moderate COVID-19, baseline IIEF-5 scores, and severe COVID-19 in patients with COVID-19 were independent risk factors for ED. A logistic regression, adjusted for age and BMI (Sansone et al .…”
Section: Discussionmentioning
confidence: 99%